CULTURAL LANDSCAPE OF THE DRÂA VALLEY, MOROCCO - Mecca, Saveiro; Baglioni, Eliana; Dipasquale, Letizia; Rkha Chaham, Khalid (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The six Drâa Valley oases are a system of several rural villages called ksur, characterized by a profound balance between agronomic, economic, social, architectural, ecological, and cultural dimensions. The Drâa valley oases are an exemplar of secular sustainable living systems and contain also a diversity of ethnic groups that deines the rich socio-cultural diversity of the area. Sophisticated irrigation systems, ruled by traditional local resource-management institutions to ensure a fair water distribution, integrated with signiicant earthen architecture, constitute a complex and important, both material and immaterial, cultural heritage. Local building technologies use raw earth as the main material; earth, due to its easy availability and its low cost, constitutes a precious resource in the building of construction elements, from the structural to the decorative. The predominantly earthenbuilding techniques, used simultaneously and symbiotically in the different architectural elements, are rammed-earth and adobe. In the Drâa Valley the cultural heritage represents an undeniable value and an excellent and competitive resource for quality, distribution, levels of preservation and permanence in today’s cultural and socio-economic structures – thus, it is a decisive element in the process of local development. Effective projects toward local development and cultural heritage conservation and innovation, in conjunction with the objective to improve living conditions of local populations, should therefore be founded on these general actions:• Identiication and systemic understanding of local, traditional and sustainable knowledge by all actors and especially by local populations;• Integration of cultural heritage with the processes of local development, in particular adapting the traditional houses into new cultural and living needs, to end the general abandonment of housing and the loss of this important heritage;• Construction of government and management systems in which the local actors know how to have dialogue and organize the real course of development, in an autonomous way, improving the speciicities of identity that characterize the place.